Novel ABCD1 mutation detected in a symptomatic female carrier of adrenoleukodystrophy. Issue 1 (17th October 2022) - Nakano, Yumiko; Taira, Yuki; Sasaki, Ryo; Tadokoro, Koh; Yunoki, Taijun; Nomura, Emi; Fukui, Yusuke; Takemoto, Mami; Morihara, Ryuta; Shimozawa, Nobuyuki; Yamashita, Toru
Abstract: We report a case of a symptomatic female carrier of X‐linked adrenoleukodystrophy (ALD) with a novel ABCD1 gene mutation. She has developed slowly progressive gait disturbance since age 40, and her father and sister had similar symptoms. When admitted to our hospital at age 66, blood analysis showed slight increase of very long‐chain fatty acids (VLCFA), and DNA analysis of ABCD1 gene revealed a novel heterozygous missense mutation (c.1700 A>C, p.Gln567Pro). The genetic testing for ABCD1 gene can be considered in female patients over middle age presenting spastic gait, because female ALD carriers tend to be symptomatic beyond age 60.